A single-cell atlas of the Culex tarsalis midgut during West Nile virus infection. - Emily A Fitzmeyer; Taru S Dutt; Silvain Pinaud; Barb Graham; Emily N Gallichotte; Jessica L Hill; Corey L Campbell; Hunter Ogg; Virginia Howick; Mara K N Lawniczak; Erin Osborne Nishimura; Sarah Hélène Merkling; et al. (PLoS Pathogens)
The mosquito midgut functions as a key interface between pathogen and vector. However, studies of midgut physiology and virus infection dynamics are scarce, and in Culex tarsalis-an extremely efficient vector of West Nile virus (WNV)-nonexistent. We performed single-cell RNA sequencing on Cx. tarsalis midguts, defined multiple cell types, and determined whether specific cell types are more permissive to WNV infection. We identified 20 cell states comprising 8 distinct cell types, consistent with existing descriptions of Drosophila and Aedes aegypti midgut physiology. Most midgut cell populations were permissive to WNV infection. However, there were higher levels of WNV RNA (vRNA) in enteroendocrine cells (EE), suggesting enhanced replication in this population. In contrast, proliferating intestinal stem cells (ISC) had the lowest levels of vRNA, a finding consistent with studies suggesting ISC proliferation in the midgut is involved in infection control. ISCs were also found to have a strong transcriptional response to WNV infection; genes involved in ribosome structure and biogenesis, and translation were significantly downregulated in WNV-infected ISC populations. Notably, we did not detect significant WNV-infection induced upregulation of canonical mosquito antiviral immune genes (e.g., AGO2, R2D2, etc.) at the whole-midgut level. Rather, we observed a significant positive correlation between immune gene expression levels and vRNA load in individual cells, suggesting that within midgut cells, high levels of vRNA may trigger antiviral responses. Our findings establish a Cx. tarsalis midgut cell atlas, and provide insight into midgut infection dynamics of WNV by characterizing cell-type specific enhancement/restriction of, and immune response to, infection at the single-cell level.